Submental intubation - Sonia Jindal; Kamlesh Kothari; Amit Kumar Singh (Wolters Kluwer Medknow Publications, 2013)
MacInnis and Baig modified Altemirs' original technique for sub-mental intubation. Instead of a lateral entry, they described a central entry just anterior to the sub-mental crease that does not carry the risk of damage to the lingual nerves, submandibular ducts and sublingual glands. We describe here our experience with this modified sub-mental intubation that also allows the operating surgeon to provide for a correct midline and optimal esthetics in case of panfacial trauma.